THE ROLE OF PARASOCIAL INTERACTION IN MEDIATING THE INFLUENCE OF VLOGGER POPULARITY AND CREDIBILITY ON PURCHASE INTENTION OF GADGET PRODUCTS - Dianthini, Putu Gita Amertadevi; Kt. Giantari, I Gst. Ayu; Rahanatha, Gede Bayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.07.TAHUN.2024, 2024)
his research examines the impact of social media on brand marketing strategies, specifically focusing on the utilization of video content displaying vloggers as influential figures. The objective of the study is to assess the relationship between popularity, credibility, and parasocial interaction towards purcase intention of reviewed product. A sample of 125 subscribers of a gadget vlogger has participated in data collection. The collected data was analyzed using the PLS-SEM method using SmartPLS 3.0. The findings indicate that credibility exerts a stronger influence on purchase intention compared to popularity. Furthermore, it was discovered that vlogger’s credibility positively and significantly affects parasocial interaction, whereas popularity does not. Parasocial interaction partially mediates the effect of vlogger’s credibility on purchase intentions. The implications of this study emphasize the importance of vlogger credibility in effectively increasing purchase intention and suggest that companies should identify credible vloggers to foster parasocial relationships with subscribers, to significantly strengthen displayed product purchase intention, particularly among subscribers.